World Heritage and Transfrontier Conservation Areas : Tourism Development and Community Participation in South Africa - Herselman, Charlene (University of Pretoria, 2022)
Mini Dissertation (MSocSci (Heritage and Cultural Tourism))--University of Pretoria, 2021.